2007
DOI: 10.1002/nau.20475
|View full text |Cite
|
Sign up to set email alerts
|

Rho-kinase and effects of Rho-kinase inhibition on the lower urinary tract

Abstract: Altered smooth muscle cell contractility/tone contributes, at least in part, to the lower urinary tract symptoms (LUTS) seen in men with benign prostatic obstruction (BPO). Accordingly, many of the therapies to date have focused largely on blockade of individual membrane receptors to diminish smooth muscle contractility and provide symptomatic relief. This pharmacologic approach has been associated with variable results, limited efficacy, and untoward side effects. Such limited clinical success is not surprisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
0
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 72 publications
1
88
0
5
Order By: Relevance
“…1,2 By reorganizing the actin cytoskeleton, Rho, a small monomeric G-protein, and the Rho-associated serine-threonine protein kinase (ROCK) pathway have been reported to participate in various cellular functions, including smooth muscle contraction, cell adhesion, and cell migration. 3,4 This pathway has also been implicated in the pathogenesis and progression of several malignant tumors, and a specific ROCK inhibitor may suppress tumor growth and metastasis. [5][6][7] The Rho/ROCK pathway has also been reported to influence, vascular smooth muscle proliferation and migration, as well as vascular smooth muscle contraction.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 By reorganizing the actin cytoskeleton, Rho, a small monomeric G-protein, and the Rho-associated serine-threonine protein kinase (ROCK) pathway have been reported to participate in various cellular functions, including smooth muscle contraction, cell adhesion, and cell migration. 3,4 This pathway has also been implicated in the pathogenesis and progression of several malignant tumors, and a specific ROCK inhibitor may suppress tumor growth and metastasis. [5][6][7] The Rho/ROCK pathway has also been reported to influence, vascular smooth muscle proliferation and migration, as well as vascular smooth muscle contraction.…”
Section: Introductionmentioning
confidence: 99%
“…␣ 1 -Adrenoceptors in prostate smooth muscle cells are coupled to Ca 2+ / calmodulin-dependent signaling via phospholipase C, and to the RhoA/Rho kinase pathway, which both lead to contraction [3] . Our results suggest that coupling of prostate ␣ 1 -adrenoceptors is not confined to these contraction-mediating signaling cascades, but that ␣ 1 -adrenoceptors in the human prostate are additionally coupled to the ERK1/2 signaling pathway, which is not involved in ␣ 1 -adrenoceptor-mediated prostate smooth muscle con- traction.…”
Section: Discussionmentioning
confidence: 99%
“…the Ca 2+ -dependent and the Rho kinase-dependent signaling cascades [3] . Studies using extraprostatic cell lines demonstrated that ␣ 1 -adrenoceptors may additionally couple to nonmotoric signaling pathways, which are involved in growth, proliferation and differentiation [4,5] .…”
mentioning
confidence: 99%
“…These compensatory changes are associated with altered expression of contractile proteins and various signalling and regulatory proteins, such as calmodulin, Rho-activated kinase and caveolins. [16][17][18][19][20] At the cellular level, muscarinic receptor-mediated bladder contraction involves two main pathways, voltage-operated Ca ++ channels and a Rho-kinase. While the opening of the sensitive Ca ++ channels allows for a marked elevation of intracellular Ca ++ concentrations resulting in contraction, the Rho-kinase constitutes a main pathway, which enhances detrusor Ca ++ sensitization necessary for the detrusor muscle to maintain contraction.…”
Section: E525mentioning
confidence: 99%
“…16 The expression of Rho-kinase is abnormally upregulated in the hypertrophied urinary bladder, resulting probably in alterations of muscle relaxation in the prostate, bladder neck and urethra in the voiding phase, as well as detrusor overactivity in the storage phase. 20 Animal studies indicate that Rho-kinase inhibitors may have a role as future treatments for bladder dysfunction. 17 Phosphodiesterase-5 inhibitors (PDE5-Is) induce down-regulation of Rho-kinase activity and this could probably explain their significant efficacy in patients with BOO.…”
Section: E525mentioning
confidence: 99%